2009
DOI: 10.1002/btpr.139
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the embryoid body microenvironment to direct embryonic stem cell differentiation

Abstract: Embryonic stem cells (ESCs) are pluripotent cells capable of differentiating into all somatic and germ cell types. The intrinsic ability of pluripotent cells to generate a vast array of different cells makes ESCs a robust resource for a variety of cell transplantation and tissue engineering applications, however, efficient and controlled means of directing ESC differentiation is essential for the development of regenerative therapies. ESCs are commonly differentiated in vitro by spontaneously self-assembling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
209
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(211 citation statements)
references
References 95 publications
2
209
0
Order By: Relevance
“…5,[30][31][32][33] As the relative effects of different microenvironmental parameters on stem cell fate are increasingly discovered, 34 it becomes important to understand how modulation of endogenous ECM and GF expression can be achieved by engineering physical forces such as hydrodynamics to direct stem cell differentiation. As indicated by the results of this study, the augmented number of genes increased in rotary environments at day 14 compared with static (Fig.…”
Section: Fig 4 Different Classes Of Extracellular Matrix (Ecm) (A-hmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[30][31][32][33] As the relative effects of different microenvironmental parameters on stem cell fate are increasingly discovered, 34 it becomes important to understand how modulation of endogenous ECM and GF expression can be achieved by engineering physical forces such as hydrodynamics to direct stem cell differentiation. As indicated by the results of this study, the augmented number of genes increased in rotary environments at day 14 compared with static (Fig.…”
Section: Fig 4 Different Classes Of Extracellular Matrix (Ecm) (A-hmentioning
confidence: 99%
“…Differentiation of PSCs in vitro can be induced by a variety of methods, the most common of which are in an adherent monolayer format 2,3 or through the formation of 3D cell spheroids in suspension culture referred to as embryoid bodies (EBs). [4][5][6] During development, cell fate specification and tissue development are achieved by the presentation of morphogenic cues in a spatiotemporally controlled, cell-mediated manner to induce differentiation and tissue formation. 7 Therefore, arrays of extracellular matrices composed of various mixtures of collagen I, collagen III, collagen IV, fibronectin, and laminin, as well as soluble factors, including wingless-type MMTV integration site family, member 3A (WNT3a), activin A, bone morphogenetic protein-4 (BMP4), and fibroblast growth factor-4 (FGF4), have been utilized to study the effects of morphogenic cues on cell phenotype during ESC differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is well known that even small and brief changes of the physical and chemical conditions of the cell environment can activate (or inhibit) signal processing for cell differentiation [4]. For instance, it has been observed that transient fluctuations in oxygen partial pressure can change gene transcription, thus influencing the fate of stem cells in culture [5].…”
Section: Introductionmentioning
confidence: 99%
“…14,[16][17][18] In particular, traditional suspension culture has given rise to EB populations which are heterogeneous in size, morphology and thus epigenetic expression, rendering them unsuitable for potential clinical applications. 2,19,20 This can be seen in previous studies indicating that suspension culture results in widely varied EB sizes (e.g. AE 60 mm for an EB of average diameter of 175 mm).…”
Section: Introductionmentioning
confidence: 56%